Dual trigger with gonadotropin-releasing hormone agonist and recombinant human chorionic gonadotropin improves the outcome of intrauterine insemination - Binarwan Halim; Hilma Putri Lubis (Obstetrics & Gynecology Science, 2022)
Objective The objective of this study was to evaluate the effectiveness of dual trigger, which is a combination of gonadotropin-releasing agonist (GnRH-a) and recombinant human chorionic gonadotropin (hCG) in the final oocyte maturation, in the outcome of intrauterine insemination (IUI). Methods This retrospective observational study was conducted from January 2016 to October 2018 and involved 639 IUI cycles at the Halim Fertility Center, Indonesia. Controlled ovarian stimulation was performed during IUI cycles. The ovulation triggers were divided into two groups: group I received a combination of GnRH-a and recombinant hCG as a dual trigger, and group II received only recombinant hCG as a single trigger. The baseline characteristics, cycle parameters, and IUI outcomes of both groups were compared. Results Our study included a total of 639 IUI cycles, 334 were in the dual trigger group and 305 in the single trigger group. The clinical pregnancy rates were significantly higher in the dual trigger group than in the single trigger group (P<0.001). Based on the multivariate analysis, the dual trigger increased the clinical pregnancy rate by 2.524 times than that by the single trigger. Conclusion Our data showed that the dual trigger combination of GnRH-a and recombinant hCG significantly improves the outcome of intrauterine insemination.